The Influence of Conditioning Agent on Phosphate Diffusion Coefficient through Polyacrylamide and Agarose Gel - Layta Dinira; Barlah Rumhayati; Rachmat Triandi Tjahjanto (The Journal of Pure and Applied Chemistry Research, 2013)
Excess phosphate in natural water can cause algae grow rapidly, to the extent causing many fish deaths that led to the extinction of certain species. Therefore, an analysis or periodic observations of phosphate levels in the water is needed. The commonly used method is diffusive gradient in thin films (DGT) technique. The DGT technique is based on the ability of analyte to diffuse through a gel, which have a value named diffusion coefficient. This research was conducted in order to study the effect of different storage solution to the phosphate diffusion coefficient through polyacrylamide and agarose gels. Initial research performed with making the polyacrylamide and agarose gels. To observe the effect of different storage solutions, the gels partly stored in distilled water gel while the others are stored in a NaCl solution of 0.01 M. Phosphate diffusion coefficient was determined using Fick's Law after analyze the phosphate concentration using UV-Visible spectrophotometer. The results showed that phosphate diffusion coefficient was highest when polyacrylamide and agarose gels stored in NaCl solution of 0.01 M.